3(3x+5)=42+3x

Simple and best practice solution for 3(3x+5)=42+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x+5)=42+3x equation:


Simplifying
3(3x + 5) = 42 + 3x

Reorder the terms:
3(5 + 3x) = 42 + 3x
(5 * 3 + 3x * 3) = 42 + 3x
(15 + 9x) = 42 + 3x

Solving
15 + 9x = 42 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
15 + 9x + -3x = 42 + 3x + -3x

Combine like terms: 9x + -3x = 6x
15 + 6x = 42 + 3x + -3x

Combine like terms: 3x + -3x = 0
15 + 6x = 42 + 0
15 + 6x = 42

Add '-15' to each side of the equation.
15 + -15 + 6x = 42 + -15

Combine like terms: 15 + -15 = 0
0 + 6x = 42 + -15
6x = 42 + -15

Combine like terms: 42 + -15 = 27
6x = 27

Divide each side by '6'.
x = 4.5

Simplifying
x = 4.5

See similar equations:

| 0=30q | | 8=3(x+5) | | 10-9+6+7*1/1+1 | | 0.25x+0.75=0.75x-2.25 | | 9.99x=6.66 | | y/15=-22 | | 6t+3= | | 3x^4-15x^3-18x^2=0 | | 0=30x | | -11.5x=34.5 | | (4x-30)=(2x) | | 1/2x^2-8=0 | | 2=x^2-10x | | 8n+3=11 | | -4x=-12+5x | | 2x+11=-5x-13 | | 18+6k=6k+6(5k+3) | | -5+8(1+5p)=123 | | n/11-6=9 | | -4+7(1+2v)=-81 | | 1.1x+2.6=0.5x-1.84 | | 4(5m+5)=160 | | w+2/3=2.5/6 | | -6(8n+5)=162 | | 2/3=2x/8 | | r/3=10/7 | | 6x+11=16-9x | | 8x^5/4x^2 | | 6x+11=16-x | | x=3*56 | | 5/m=2/5 | | 2n+5=12 |

Equations solver categories